Implementación de un programa neuropsicológico para mejorar la regulación emocional en niños con problemas de conducta - Illescas Quezada, Isabella Beatriz; Cárdenas Cueva, Dayana Nicole (My University, 2025)
Through a systematic intervention process in the educational context of the "Enriqueta de Wind de Laniado" Elementary School, located in Machala, Ecuador, a neuropsychological program was implemented and evaluated to strengthen emotional regulation in children between 7 and 11 years old with behavioral problems. The research adopted a qualitative methodology enriched with quantitative tools, utilizing in-depth interviews, focus groups, direct observation, and psychometric instruments such as the Special Educational Needs Detection Form from the Ministry of Education of Ecuador; the Child and Adolescent Assessment System (SENA), in its Primary Self-Report and Primary Family versions; the Emotion Regulation Questionnaire (ERQ); and the Scale for the Assessment of Attention Deficit Hyperactivity Disorder (EDAH) for teachers. The results showed a high prevalence of disruptive behaviors such as aggression, disobedience, and difficulties in emotional recognition, associated with the family environment, dysfunctional parenting styles, and sociocultural factors. The implementation of the program demonstrated significant improvements in emotional self-regulation and a decrease in problematic behaviors, consolidating the effectiveness of early neuropsychological strategies. It is concluded that children's emotional regulation is a complex process linked to the development of executive functions, neurological maturation, and the influence of the family environment. Addressing this process in schools helps promote children's psychological and social well-being.
A través de un proceso sistemático de intervención en el contexto educativo de la Escuela de Educación Básica “Enriqueta de Wind de Laniado”, ubicada en Machala, Ecuador, se puso en práctica un programa neuropsicológico orientado a fortalecer la regulación emocional en niños de entre 7 y 11 años con problemas de conducta. La investigación adoptó una metodología cualitativa enriquecida con herramientas cuantitativas, empleando entrevistas a profundidad, grupos focales, observación directa e instrumentos psicométricos como la Ficha de Detección de Necesidades Educativas Especiales del Ministerio de Educación del Ecuador, El Sistema de Evaluación de Niños y Adolescentes (SENA) en sus versiones Primaria Autoinforme y Primaria Familia, El Cuestionario de Regulación emocional (ERQ), y la Escala para la Evaluación del Trastorno por Déficit de Atención con Hiperactividad (EDAH) para docentes. Los resultados evidenciaron una alta prevalencia de conductas disruptivas como agresividad, desobediencia y dificultades en el reconocimiento emocional, asociadas al entorno familiar, estilos de crianza disfuncionales y factores socioculturales. La implementación del programa demostró mejoras significativas en la autorregulación emocional y disminución de conductas problemáticas, consolidando la eficacia de estrategias neuropsicológicas tempranas. Se concluye que la regulación emocional infantil es un proceso complejo vinculado al desarrollo de funciones ejecutivas, la maduración neurológica y la influencia del entorno familiar, cuya atención desde el ámbito escolar permite promover el bienestar psicológico y social de los niños.
Keywords: REGULACIÓN EMOCIONAL; NEUROPSICOLOGÍA INFANTIL; INTERVENCIÓN EDUCATIVA; FUNCIONES EJECUTIVAS